Industrial Processing Induces Pericardial Patch Degeneration - Peivandi, Armin Darius; Martens, Sven; Heitplatz, Barbara; Guseva, Alena; Mueller, Klaus-Michael; Martens, Sabrina (Frontiers in Surgery, 2022)
Background. Autologous pericardium is considered gold standard for various reconstructive surgical procedures in children. However, processed bovine, equine, and porcine pericardial tissue are also widely used. We investigated structural differences and analyzed alterations caused by industrial processing. Additionally human and equine pericardium explants, used during aortic valve reconstruction were analyzed. Methods. Pericardial tissues (native, processed and explanted) were gathered and stained with HE and EvG to visualise collagen as well as elastic fibers. Fiber structures were visualized by light and polarisation microscopy. Antibody staining against CD 3, CD 20, and CD 68 was performed to identify inflammation. Results. Native pericardium of different species showed small differences in thickness, with bovine pericardium being the thickest (bovine: 390 µm (± 40.6 µm); porcine: 223 µm (± 30.1 µm); equine: 260 µm (± 28.4 µm)). Juvenile pericardium was 277 µm (± 26.7 µm). Single collagen bundle diameter displayed variations ( 3 µm – 20 µm). Parallel collagen fibers were densely packed with small inter-fibrillary space. After industrial tissue processing, loosening of collagen network with inter-fibrillary gapping was observed. Pericardium appeared thicker (mean values ranging from 257 µm – 670 µm). Processed tissue showed less birefringence under polarized light. All analyzed tissues showed a small number of elastic fibers. Fibrosis, calcification and inflammatory processes of autologous and equine pericardium were observed in patient explants. Conclusion. None of the analyzed tissues resembled the exact structure of the autologous pericardial explant. Degeneration of pericardium starts during industrial processing, suggesting a potential harm on graft longevity in children. A careful surgical approach prior to the implantation of xenografts is therefore needed.